Adaptasi Masyarakat Terhadap Banjir Disekitar Pinggiran Sungai - Nur Leli; La Harudu; Surdin; La Ode Nursalam (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2024)
Pudahoa Village has a river that is prone to flooding and can cause losses to the people living around the river. This research aims to determine the factors that cause flood disasters and the adaptation of the Pudahoa Village community to flood disasters around the riverbanks of Pudahoa Village, Mowila District, Konawe Selatan Regency. This type of research uses a qualitative descriptive research method with research subjects totaling 20 people who were determined using a purposive sampling technique. The data collection techniques used were observation, interviews, and documentation. The research results show that: 1) the main cause of flooding in Pudahoa village is high rainfall and the intensity of rainfall; 2 Community adaptation to flood disasters is carried out in three stages, namely: a) prevention in the form of building embankments and raising house foundations; b) handling such as disseminating flood information through sirens or gongs; and c) restoration of roads, houses and river bodies